2012
DOI: 10.5489/cuaj.141
|View full text |Cite
|
Sign up to set email alerts
|

Study comparing the applicability of dorsal lumbotomy in older children

Abstract: Objective: Dismembered pyeloplasty through dorsal lumbotomy to correct ureteropelvic junction obstruction is mainly successfully performed in children under 5 years old for technical reasons. We compared children who underwent dorsal lumbotomy by age group (<5 vs. ≥5 years old) to determine if the surgical success and long-term results were comparable. Materials and Methods:We retrospectively reviewed the charts of 134 children undergoing a pyeloplasty. Group 1 consisted of children <5 years old (n = 90) and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The study concluded that dismembered pyeloplasty is effective and safe in the young and older children. [18] A study with 59 children with median age 5.7 years who underwent transverse dorsal lumbotomy. Median time was 78 minutes and median length of incision was 3-5 cm.…”
Section: Dorsal Lumbotomymentioning
confidence: 99%
“…The study concluded that dismembered pyeloplasty is effective and safe in the young and older children. [18] A study with 59 children with median age 5.7 years who underwent transverse dorsal lumbotomy. Median time was 78 minutes and median length of incision was 3-5 cm.…”
Section: Dorsal Lumbotomymentioning
confidence: 99%
“…Some authors defend selecting the cases in which dorsal lumbotomy can be applied, not being useful in obese children. 2 What is missing in the work we are commenting on is the way in which the authors handle the polar vessels through this dorsal access. One of the basic principles of dismembered pyeloplasty is the transposition of the crossing vessels.…”
mentioning
confidence: 99%
“…Ureteropelvic junction obstruction (UPJO) is the most common cause of HDN in children. The choice of surgery is dismembered pyeloplasty that can be done by anterior subcostal, flank approach or dorsal lumbotomy approach [1,2]. The posterior vertical lumbotomy incision provides an easy and quick access to UPJ.…”
Section: Introductionmentioning
confidence: 99%